Thiol metabolic changes induced by oxidative stress and possible role of b-vitamins supplements in esophageal cancer patients - Burini, Roberto Carlos [UNESP]; Lamônica, Vânia Cristina [UNESP]; Moreto, Fernando [UNESP]; Yu, Yong-Ming; Henry, Maria Aparecida Coelho Arruda [UNESP] (My University, 2015)
Rationale: Reduction-oxidation reactions determine cell homeostasis and free-radicals productions are invariable components of the aerobic metabolism processes. The cells have an elaborate defense against free-radicals and the imbalance resulting in excessive accumulation of free-radicals, defined as oxidative stress which plays a key role in promotion of pathological processes including cancer. Hence physiological levels of free-radicals mediate crucial intracellular signaling pathways and are essential for cell survival whereas excess generates cell damage and death. Thereby, hormetic responses to free-radicals are resulting from the constant ongoing battle between the production of oxidants and the antioxidants defenses. Among the oxidative stress-dependent compounds are the thiol-antioxidants having glutathione (GSH) as its major representative intracellularly. Alterations in GSH levels are associated with human diseases including cancer where it has double-edge sword actions by protecting non-tumor cells against oxidative stress and by removal and detoxification of carcinogens. However, at the other end of the scale GSH protects tumor cells from apoptosis by increasing the resistance to cancer chemotherapeutic agents. By its physiological importance GSH levels can be controlled endogenous and exogenously by changing its biosynthesis with nutrients such as amino acids and vitamins. Almost none has been found in the available literature about B vitamin related-GSH metabolism in esophageal cancer. Nutritional deficits in fresh fruits, vegetables and dietary fiber are commonly referred as associated with the presence of esophagus cancer (EC). Moreover heavy consumption of alcoholic beverages and tobacco might interfere with vitamins and dietary components with potential anti-carcinogenic effects. To our understanding the adequacy of B-vitamins would allow the full effects of the sulfur-containing antioxidative defenses. Methods: Twenty-six patients with EC (58.4 ± 11.8 years) and a control group of 20 healthy subjects (27 ± 8.4 years) were assessed for nutritional and biochemical markers at baseline (Mo). The EC patients were distributed in two groups G1/G2 to be either supplemented with placebo or vitamins B2, B6, B12 and folate during 15 days (M1) followed by cross-over for the same period (M2). The results were statistically analyzed. Results: The EC patients were predominantly males addict to smoke and alcoholism, diagnosed with squamous-cell carcinoma, stage IV. Their food intake was inappropriate, particularly energy resulting in 46% with Body Mass Index (BMI) <18 kg/m2 (15.9 ± 1.7 kg/m2) presenting a body-weight loss of 21.3 ± 13.4% during the last 6 months. However plasma albumin and glucose were similar to controls. No significant difference was also found for cholesterol, folate, and levels of Methionine (Met), Homocysteine (Hcy), Glutamic acid (Glu), and in the glutathione disulfide/glutathione ratio (GSSG/GSH). After the intervention it was observed an increasing of B12 vitamin and decreased levels of Hcy. Conclusion: EC in its advanced stage has a different pattern of thiol pathways with the most preserved amino acids being methionine, homocysteine and glutamate. Met/Hcy (transmethylation/remethylation) cycle was maintained whereas Hcy/Cys (transsulfuration) was reduced therefore accumulating Hcy. However even in the presence of lower Cys it seems that there is an effort of the host to generate GSH by uptaking more GSH- precursors (Cys and Glu) from the GSH-gamma GT cycle for keeping controlled the GSSG/GSH ratio. Short-term B-vitamin supplementation led to increased plasma vitamin B12 which together with normal folate contributed effectively for reducing Hcy. By keeping controlled Hcy and GSH/GSSG the cell would tend to reduce the oxidative stress and probably the tumor progression, what could be attributed presently to the supplemented vitamins.
Keywords: B-vitamin supplementation in esophageal cancer; Cell oxidation-reduction homeostasis; Dietary risk factors for esophageal cancer; Oxidative stress in cancer; sulfur antioxidant pathway in esophageal cancer